The efficiency of barangay peacekeeping action team (BPAT) and the level of prevention of juvenile delinquency in Poblacion Uno, Bansalan Davao del Sur - Malik, Jasper L.; Estomo, Reyland A.; Gantuangco, Ching Jay E. (--Davao del Sur: UM Bansalan College, 2011)
This study used descriptive research to identify the cases filed to the juvenile delinquents. It is descriptive because the data is presented in qualitative and quantitative description of the Efficiency of the BPAT's and the Level of Prevention of juvenile delinquency.